Effects of GandhPaalashi (Hedychium spicatum) on the expression of hepatic genes associated with biotransformation, antioxidant and immune systems in WLH cockerels fed indoxacarb - CHOUDHARY, GOVIND KUMAR; SINGH, SATYA PAL; KUMAR, AMIT (The Indian Journal of Animal Sciences, 2018)
The objective of the present study was to evaluate the efficacy of Hedychium spicatum (HSRP) root powder, to ameliorate changes in gene expression in WLH cockerels fed indoxacarb. After 16 weeks of treatment, all birds from different groups were sacrificed humanly and collected the liver pieces in RNA later for expression study by RT-PCR to evaluate changes in the expression of genes involved in antioxidant function [catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione S-transferase (GST)], biotransformation [cytochrome P450 1A1 (CYP1A1)], and the immune system [interleukins 6 (IL-6)]. Changes in gene expression were determined using the quantitative real-time PCR technique. There were significant upregulation of IL-6, CYP1A1 and GPx genes in indoxacarb treated groups. There was significant down regulation of CAT and SOD genes in indoxacarb treated groups in comparison to control. Simultaneous treatments with HSRP produce ameliorative effect and restore the gene activities at par with control. The current study demonstrates protective effects of HSRP on changes in expression of antioxidant, biotransformation, and immune system genes in cockerels fed indoxacarb.